2022
DOI: 10.1021/acs.est.2c00031
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Arsenic Capture in Flue Gas by CuCl2-Modified Halloysite Nanotube Composites with High-Temperature NOx and SOx Resistance

Abstract: Gaseous arsenic emitted from coal combustion flue gas (CCFG) causes not only severe contamination of the environment but also the failure of selective catalytic reduction (SCR) catalysts in power plants. Development of inexpensive and effective adsorbents or techniques for the removal of arsenic from high-temperature CCFG is crucial. In this study, halloysite nanotubes (HNTs) at low price were modified with CuCl2 (CuCl2–HNTs) through ultrasound assistance and applied for capturing As2O3(g) in simulated flue ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Similar to the Cl − analysis (Table 8), the effect of SO 4 2− concentration on As removal was insignificant. Regarding adsorption mechanism of SO 4 2− , some researchers believe that ligand displacement plays a vital role, whereas others hold that it is similar to minor electrostatic adsorption mechanisms involving Cl − and NO 3 − 32–34 . The experimental results are consistent with Section 3.5.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to the Cl − analysis (Table 8), the effect of SO 4 2− concentration on As removal was insignificant. Regarding adsorption mechanism of SO 4 2− , some researchers believe that ligand displacement plays a vital role, whereas others hold that it is similar to minor electrostatic adsorption mechanisms involving Cl − and NO 3 − 32–34 . The experimental results are consistent with Section 3.5.…”
Section: Resultssupporting
confidence: 78%
“…− . [32][33][34] The experimental results are consistent with Section 3.5. In this study, SO 4 2ions were possibly attached to the surface of desulfurization slag samples by minor electrostatic force, which could not compete with arsenate ions during coordinate covalent bonding.…”
Section: Nosupporting
confidence: 88%
“…Figure a shows the FTIR spectra of HNTs and SrFeO 3‑δ . The peaks at 540, 922, 1640, and 3458 cm –1 resulted from the Al–OH bending bands, deformation vibration of Al–O–Si, and O–H stretching of H 2 O and HNTs, respectively. , The presence of peaks at 3642 and 3711 cm –1 was attributed to the vibration of the inner hydroxyl groups of halloysite. , The adsorption bands at 616 and 707 cm –1 ascribed to stretching and bending vibrations of Fe–O from SrFeO 3‑δ . Li et al thought that SrO was not stable, resulting in no peak of Sr–O at ∼400 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…18 Our team-prepared Fe 3 O 4 @SiO 2 @Cu-MHNTs and CuCl 2 -HNTs were used to deal with elemental mercury and gaseous arsenic, respectively, showing super adsorption performance. 15,19 Besides, the surface chemical structures of alumina octahedral layers and rolling silica tetrahedral layers in HNTs can stimulate interfacial electron dynamics transmission, declining the electron−hole recombinations. 16 This further confirmed that HNTs as carriers were feasible for the photocatalytic performance of SrFeO 3-δ .…”
Section: Introductionmentioning
confidence: 99%
“…3− is generally considered to be carried out by the mechanism of ligand substitution, 39,40 and a strong covalent bond is formed on the surface of the adsorbate. The Cl − and Mg 2+ selected in this study are all adsorbed on the surface of BOFS by relatively weak electrostatic force.…”
Section: 8mentioning
confidence: 99%